Identification of variations in the onset of the rainy and dry seasons in Indonesia - Riza Adriat; Aprilina Aprilina; Haries Satyawardhana; Andi Ihwan; Yuris Sutanto (Journal of Bioresources and Environmental Sciences, 2025)
In the equatorial region, Indonesia experiences distinct wet and dry seasons influenced by monsoon. The country's agricultural sector is highly susceptible to the impacts of climate change, including extreme weather events and shifting seasonal patterns due to global warming. This study aims to analyze variations in rainfall intensity and their effects on the onset of the seasons in Indonesia from 2001 to 2022. The research used GSMaP data, focusing on the area between 6° N - 11° S and 95° - 141° E. The start of the season was determined based on rainfall criteria from BMKG. The findings reveal significant changes in the onset of the rainy and dry seasons in regions such as Sumatra and Kalimantan, with the maximum change being 8 dasarian. The study also indicates that the rainy season during the 2012-2022 period is shorter compared to the 2001-2011 period, resulting in a longer dry season. Furthermore, the maximum standard deviation is 14 dasarian, allowing the season's start to shift by up to 14 dasarian annually in certain areas of Indonesia. ENSO can influence changes in the pattern of the start of the season.